(untitled) (LingPoet: Journal of Linguistics and Literary Research, 2022)
Abstract. As an opportunity to promote his ideas and gain public support, Joe Biden, as the president of America conveyed a message of hope and unity in his inaugural address. Taken this as a consideration, this investigation tries to reveal the use of Mood system, Transitivity system as well as to determine the use of both to convey his political intention/message in the address. It is a qualitative research transcription of the speech used as the main source of data. The first finding shows that in total of 280 clauses, 269 data belong to Indicative Mood and 11 data belong to Imperative Mood. In terms of Transitivity, all types appeared in the address with the most dominated process is Material Process. In this case, Material Process as the most dominated Transitivity type, was functioned to portray a new government under his rule and offer answers to the country’s issues. Regarding the Mood finding, it was found that Joe Biden frequently used pronoun “we”, “our” and “us” to show that the nation belongs to every person in America.